USAGE AND EFFECTIVENESS OF FERTILITY ENHANCEMENT TECHNIQUES AMONG SMALL-HOLDER FARMERS IN THE KANO CLOSE SETTLED ZONE, KANO STATE (FUDMA JOURNAL OF SCIENCES, 2020)
This study examines the usage and effectiveness of diverse soil fertility enhancement technique (SFET) among smallholder farmers in the Kano close-settled zone.  Four study villages were selected from different parts of the Kano Close-Settled Zone, Kano state. A multi- stage sampling technique was used in selecting a total of 112 farmers for the study. Data were collected by means of structured questionnaires and analyzed using descriptive statistics. The result shows that 88.4% of the respondents are in the range of 21 to 50 years, which is active age group. The mean age of the respondents was 40 years.The result reveals that small ruminants manure with a total of 94% was ranked first in term of popularity in usage and effectiveness in fertility enhancement, ashes manure ranked second. Cattle dung manure and Grasses and compound sweeping manure became the third popular and effective techniques among the respondents. However, inorganic fertilizer is largely utilized by most of the farmers more especially NPK (93%) and Urea (93%) which shows that majority of the respondents combined the use of both organic manure and inorganic fertilizers. In terms of agronomic practices, majority of the respondents practice mixed cropping and intercropping (88%) and crop rotation (86%). It is therefore recommended that farmers should always be encouraged in the appropriate adoption of both the modern and indigenous soil fertility enhancement techniques.
Keywords: Soil, fertility, enhancement technique, small scale farmers